Assessment of Radiation Dose in Computed Tomography for Routine Brain and Abdomen Examinations - Julien, Siriwan; Mueangsawang, Sayan (Journal of Health Science of Thailand, 2017)
Computed tomography (CT) is a medical imaging procedure that can produce cross section images of human body and provides better visualization of soft tissue; making it widely used in clinical practice. The device emits relatively high radiation dose which may be harmful to patients. Therefore, there is a need to adjust the device so as to obtain good quality imaging at minimal radiation dosage. The purpose of this study was to evaluate radiation dose in routine brain and abdomen examinations among 9 CT units in provincial and private hospitals in Trang, Krabi, Phang-nga and Phuket provinces during June -August 2012. The weighted CTDI were tested by using PMMA head and body phantom recommended by International Atomic Energy Agency, then dose length product (DLP) values were calculated. It was found that the DLP for brain and abdomen examinations for 60 +/- 15kg sized patients were in the ranges of 416.9 - 1,528.8 and 462.0 - 1,473.8 mGy-cm respectively, and the third quartile of the group were 1,160.7 and 1,106.7 mGy-cm respectively, which higher than the dosage set in the European guidelines (the DRLs were 1,050.0 and 780.0 mGy-cm respectively). When compared by unit found 4 and 5 units for head and abdomen examination had the values higher than the reference’s. The results indicated the need for radiographers to review and set the dosage in order to reduce radiation exposure to patients.